Original article Presence of L-kynurenine aminotransferase III in retinal ganglion cells and corpora amylacea in the human retina and optic nerve - Rejdak, Robert; Rummelt, Carmen; Zrenner, Eberhart; Grieb, Pawel; Rejdak, Konrad; Okuno, Etsuo; Thaler, Sebastian; Nowomiejska, Katarzyna; Kruse, Friedrich; Turski, Waldemar; Junemann, Anselm GM (Folia Neuropathologica, 2011)
Background : Corpora amylacea (CAm) are a hallmark of aging and neurodegeneration. The presence of kynurenine aminotransferases I and II (KAT I and II) in CAm in the human retina and optic nerve has been already shown. The present study aimed to examine kynurenine aminotransferase III (KAT III) immunoreactivity in CAm in the human retina and optic nerve. Material and methods : Polyclonal antibody against KAT III was used on sections of human eyes enucleated due to malignant uveal melanoma. PAS-stained sections of CAm were compared with KAT III stained ones. Results : KAT III immunoreactivity was observed in CAm in the retina, prelaminar, laminar and retrolaminar region of the optic nerve with similar location to PAS-stained sections. The most intense staining was observed in the retrolaminar part of the optic nerve. KAT III immunoreactivity was also present in the cytoplasm of retinal ganglion cells. Conclusions : Expression of KAT III in CAm in the human retina and optic nerve indicates that this enzyme may be relevant in mechanisms of neurodegeneration leading to CAm formation.